2022
DOI: 10.3390/ijms23105556
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Human Neutralizing mAb Recognizes Delta, Gamma and Omicron Variants of SARS-CoV-2 and Can Be Used in Combination with Sotrovimab

Abstract: The dramatic experience with SARS-CoV-2 has alerted the scientific community to be ready to face new epidemics/pandemics caused by new variants. Among the therapies against the pandemic SARS-CoV-2 virus, monoclonal Antibodies (mAbs) targeting the Spike glycoprotein have represented good drugs to interfere in the Spike/ Angiotensin Converting Enzyme-2 (ACE-2) interaction, preventing virus cell entry and subsequent infection, especially in patients with a defective immune system. We obtained, by an innovative ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…We found that the high affinity binding of these mAbs to the Omicron variant is not retained, as no significant signals were observed at pM and low nM concentrations ( Figure 1 ). Thus, we tested them at higher concentrations in comparison with D3 mAb, which was reported to retain the ability to bind the Spike-Omicron variant in the nanomolar range [ 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the high affinity binding of these mAbs to the Omicron variant is not retained, as no significant signals were observed at pM and low nM concentrations ( Figure 1 ). Thus, we tested them at higher concentrations in comparison with D3 mAb, which was reported to retain the ability to bind the Spike-Omicron variant in the nanomolar range [ 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…To this aim, it could be useful to identify novel specific mAbs binding to unmutated epitopes of novel VOCs Spike-RBD or to combine different mAbs in order to potentiate their antiviral efficacy against new emerging variants. Here, we further characterized D3, a novel human mAb previously generated in our laboratory and characterized for its activity against the wild-type virus (Wuhan, China), UK, Delta and Gamma variants [ 17 , 18 ]. The aim was to investigate its ability to recognize also the other emerged Omicron subvariants to potentiate the therapeutic efficacy in combination with the approved mAbs or to exploit it for potential diagnostic applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variable region of Sotrovimab binds to a highly conserved epitope of the SARS-CoV-2 spike protein in a region outside the highly mutagenic ACE2 receptor binding motif (Kd = 0.21 nM) and does not compete with human ACE2 receptor binding [ 148 ]. The highly conserved epitope targeted by Sotrovimab has been found on 99.8% of SARS-CoV-2 viruses which allows its use against mutagenic variants, including Omicron [ 149 ]. In May 2021, Sotrovimab received an Emergency Use Authorization in the United States for the treatment of mild to moderate SARS-CoV-2 in higher risk patients to prevent progression to severe symptoms [ 148 ].…”
Section: Resultsmentioning
confidence: 99%
“…This highlighted the necessity of active, ongoing monitoring of mAB efficacy and amending treatment options accordingly based on the main variant causing SARS-CoV-2 infections. For the BA.2 sublineage, this includes use of bebtelovimab (LY-CoV1404) [17], or considering combination therapy with sotrovimab to ensure a broader spectrum of cover [18]. Overall, during the Delta pandemic, mAbs generally held significant promise in neutralizing the SARS-CoV-2 virus.…”
Section: Reviewmentioning
confidence: 99%